The Origins of the Canon of the Hebrew Bible: An Analysis of Josephus and 4 Ezra - Ossándon, Juan Carlos (Supplements to the Journal for the Study of Judaism Ser, 2018)
Intro -- Contents -- Acknowledgments -- Introduction -- Introductory Note -- Chapter 1 A Status Quaestionis on the Formation of the Canon of the Hebrew Bible -- 1.1 The Date of Origin of the Jewish Canon -- 1.1.1 The Evidence of Qumran -- 1.1.2 Other Evidence of the First Century CE -- 1.2 The Problems Concerning Yavneh -- Chapter 2 Some Preliminary Clarifications -- 2.1 The Codex -- 2.2 The Printing Press -- 2.3 "Hebrew Bible" -- 2.4 "Canon" -- Chapter 3 Methodology and Structure -- Part 1 The Twenty-Two Books of the Jews According to Josephus -- Introductory Note -- Chapter 4 The Passage of the Against Apion -- 4.1 The Text -- 4.2 Possible Identification of the Twenty-Two Books -- 4.3 The Prophets and Their Succession -- 4.3.1 The Cessation of Prophecy? -- 4.3.2 Priests, Philosophers, and Historians -- 4.3.3 The Interruption of the Prophetic Succession -- 4.3.4 The Prophet Josephus? -- 4.4 Assimilation of the Books to the Sacredness of the Torah -- 4.5 Summing-Up -- Chapter 5 The Twenty-Two Books outside the Against Apion -- 5.1 The Scriptures in the Jewish War -- 5.2 The Jewish Antiquities -- 5.2.1 The Twenty-Two Books -- 5.2.2 The Succession of Prophets -- 5.3 The Life -- Chapter 6 Josephus and Some Books on the Borderline of the Canon -- 6.1 Daniel -- 6.2 First Esdras, Ezra, and Nehemiah -- 6.3 Esther -- 6.4 Tobit and Judith -- 6.5 Letter of Aristeas, 1 Maccabees, and 2 Maccabees -- 6.6 The Book of Jubilees and the Temple Scroll -- 6.7 The Apocalyptic Literature and the Case of 1 Enoch -- Part 2 The Ninety-Four Books of the Torah According to 4 Ezra -- Introductory Note -- Chapter 7 Introduction to 4 Ezra -- 7.1 Title, Literary Genre, and Jewish Character -- 7.2 Text and Transmission -- 7.3 Date and Place of Composition -- 7.4 Fourth Ezra and 2 Baruch -- 7.5 Structure and Summary of the Content